PEMETAAN PERKEMBANGAN PERHOTELAN DI PUSAT PERDAGANGAN DAN JASA KOTA SEMARANG DENGAN SISTEM INFORMASI GEOGRAFIS - Andi Hermawan; Joesron Alie Syahbana (Department of Urban and Regional Planning, Diponegoro University, 2015)
The expanded growth of the trade and services area of Peterongan - Tawang – Siliwangi (Petawangi) in Semarang City has resulted in a new growth of commercial center activity within the area. Hotels as one of the potential trade and service components in the center of the area have an important role in the Semarang economy. The growth of hotels is due to the growth of activities like meeting, incentives, conference, and exhibition (MICE) as an effect of business activities in Semarang City. The share of hotels in the Petawangi area is around 70 percent of the total hotel tax in Semarang City. The purpose of this research is to identify the characteristics of the growth of hotels in the Petawangi Area during the last 3 years (2011-2014). The research has used spatio-temporal GIS and qualitative analysis, utilizing snowball sampling technique. The results show that the growth of hotels is excessive in the sense that the supply of hotel rooms exceeds the demand. The hotel growth is most intense in the urban villages of Sekayu and Pekunden. The emergence of the national government policy, which does not support the development of city hospitality through MICE, may result in a decrease of the hotel tax in Semarang for about 35 to 50 percent per year. To be able to keep the balance between supply and demand, better cooperation between the Semarang City government and the hotels managements is needed. It is especially for developing the infrastructure such as integrated inter-modal transportation for easier access to and from airport, improvement of urban facilities, city tourism development, and organizing national events to increase the declining demand of MICE. © 2015 GJGP UNDIP. All rights reserved